Introducing hepatitis C virus healthcare pathways in addiction care in the Netherlands with a Breakthrough project: a mixed method study - Patricia A. M. Kracht; Elisabeth A. de Gee; Agnes van der Poel; Marc A. M. T. Verhagen; Andy I. M. Hoepelman; Esther A. Croes; Joop E. Arends (BMC, 2019)
Abstract Background People who inject drugs (PWID) are disproportionally affected by the hepatitis C virus (HCV) infection. In the Netherlands, active HCV transmission in PWID has practically been halted but uptake of HCV testing and linkage to care remains insufficient in this risk group. A national HCV in Addiction Care (HAC) quality improvement project based on the Breakthrough methodology (i.e. Breakthrough project) aimed to secure proper linkage to care in PWID by introducing local HCV healthcare screening and treatment pathways in addiction care units. Aim To qualitatively appraise the local HCV healthcare pathways; to evaluate the yield in terms of number of PWID screened, diagnosed, referred, and treated; and to identify best practices and barriers to successful participation in the HAC Breakthrough project. Methods Between 2013 and 2016, 12 units of addiction care centers throughout the Netherlands participated in two series of a HAC Breakthrough project. Local multidisciplinary teams created HCV healthcare pathways. Quality assessment of HCV healthcare pathways was performed retrospectively and data on screening results was collected. In-depth interviews were conducted to elucidate best practices and essential elements for successful participation. Results In total, six HCV healthcare pathways were submitted by ten teams of which 83% was judged to be of "good" or "sufficient" quality. Uptake of HCV-antibody screening was 40% (N = 487/1219) and uptake of HCV-RNA in HCV-antibody positives was 59% (N = 107/181). The project resulted in 76 (6%) newly detected cases of persistent HCV viremia. Of all HCV-RNA positives, 92% was referred to a hepatitis treatment center. In 39% (N = 27/70) of those referred, treatment initiation was documented and 82% (N = 22/27) achieved a sustained virological response. Teams identified several best practices including motivational counseling training, oral swabs for anti-HCV testing, facilitating complementary HCV RNA testing, and supervised hospital visits. Conclusion The HAC Breakthrough project has brought about good quality HCV healthcare pathways in the majority of participating addiction care centers and has successfully linked PWID with ongoing HCV viremia to care. Uptake of HCV screening and treatment after referral were identified as the main gaps to be closed in the HCV cascade of care to achieve final HCV elimination in Dutch PWID (i.e. micro-elimination).